1994
DOI: 10.1128/iai.62.1.194-202.1994
|View full text |Cite
|
Sign up to set email alerts
|

Direct activity of human T lymphocytes and natural killer cells against Cryptococcus neoformans

Abstract: Lymphocytes constitute a critical component of host defenses against cryptococcosis. Previously, we demonstrated that human lymphocytes cultured with interleukin-2 formed conjugates with, and directly inhibited the growth of, Cryptococcus neoformans. Here, we explore the anticryptococcal activity of freshly isolated, highly purified populations of human peripheral blood lymphocytes. Lymphocytes were incubated with encapsulated C. neoformans for 24 h, after which the lymphocytes were lysed, dilutions and spread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
1
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 41 publications
(59 reference statements)
1
78
1
2
Order By: Relevance
“…Recent studies indicated that human NK cells and T cells had direct activity in vitro against Cne (Levitz et al, 1994;Murphy et al, 1993), although there was conflicting evidence that human NK cells had no growth-inhibiting activity unless antibody against the organism was present (Miller et al, 1990). We demonstrated that murine NK cells had a minor effect against the organism following iv inoculation, but failed to play a role in early lung clearance if the organism was inoculated via the trachea .…”
Section: Cryptococcus Neoformansmentioning
confidence: 71%
“…Recent studies indicated that human NK cells and T cells had direct activity in vitro against Cne (Levitz et al, 1994;Murphy et al, 1993), although there was conflicting evidence that human NK cells had no growth-inhibiting activity unless antibody against the organism was present (Miller et al, 1990). We demonstrated that murine NK cells had a minor effect against the organism following iv inoculation, but failed to play a role in early lung clearance if the organism was inoculated via the trachea .…”
Section: Cryptococcus Neoformansmentioning
confidence: 71%
“…T cells and NK cells have direct anti-cryptococcal activity. In vitro, CD4 + and CD8 + T lymphocytes directly inhibit fungal growth by attaching to the cryptococcal cell surface (Murphy et al, 1993;Levitz et al, 1994). Binding of NK cells to the fungus and release of cytolytic compounds leads to direct killing.…”
Section: Cryptococcus Neoformansmentioning
confidence: 99%
“…Experimental studies have shown that CD4 T lymphocyte depletion leads to the dissemination of C. n e o f o m n s from the lungs [22], and CD8 T cell depletion impairs clearance of both avirulent and virulent strains from the lungs [3,4]. CD4 and CD8 T cells also have a fungistatic activity, by direct contact with cryptococci [23]. In our study, the failure of MAIDS-induced immunosuppression to affect the control of C. neoformans could be related to the lack of decrease in CD4+ and CD8+ cells in blood (data not shown) and spleen ( Table 3).…”
Section: Discussionmentioning
confidence: 99%